Small-Bowel Capsule Endoscopy in Patients with Suspected Crohn's Disease—Diagnostic Value and Complications. (20th July 2010) - Figueiredo, Pedro; Almeida, Nuno; Lopes, Sandra; Duque, Gabriela; Freire, Paulo; Lérias, Clotilde; Gouveia, Hermano; Sofia, Carlos
Abstract : Background . The aim of this work was to assess the value of capsule enteroscopy in the diagnosis of patients with suspected Crohn's Disease (CD). Methods . This was a retrospective study in a single tertiary care centre involving patients undergoing capsule enteroscopy for suspected CD. Patients taking nonsteroidal anti inflammatory drugs during the thirty preceding days or with a follow-up period of less than six months were excluded. Results . Seventy eight patients were included. The endoscopic findings included mucosal breaks in 50%, ulcerated stenosis in 5%, and villous atrophy in 4%. The diagnosis of CD was established in 31 patients. The sensitivity, specificity, positive and negative predictive value of the endoscopic findings were 93%, 80%, 77%, and 94%, respectively. Capsule retention occurred in four patients (5%). The presence of ulcerated stenosis was significantly more frequent in patients with positive inflammatory markers. The diagnostic yield of capsule enteroscopy in patients with negative ileoscopy was 56%, with a diagnostic acuity of 93%. Conclusions . Small bowel capsule endoscopy is a safe and valid technique for assessing patients with suspected CD. Capsule retention is more frequent in patients with positive inflammatory markers. Patients with negative ileoscopy and suspected CD should be submitted to capsule enteroscopy.